The relationship between angular displacement of the hammer in the double support phase and its velocity in the hammer - Ruiz, F. J. R.; Davila, M. G. (Journal of Human Sport & Exercise, 2009)
The present study arises as a response to the historical controversy about the theoretical model of the hammer throw and performance. It starts from the fluctuations produced in the tangential velocity in the centre of gravity (CG) of the hammer in each turn, accelerating during the double support phase and reducing markedly in the single support phase. Coaches have sought to prolong the double support phase, although other studies have shown that acceleration is also possible during the single support phase. It has recently been proved that to the extent that the velocity of the CG of the hammer increases, the time that the thrower remains in the double support phase tends to reduce. The action of thirty hammer throwers in five national and international competitions has been analysed, utilizing the methodology proposed by Dapena (1984) and Gutiérrez, Soto & Rojas (2002) of 3D photogrammetric techniques. The results show a correlation between the angular displacement of the hammer during the double support phase and its average velocity in the penultimate turn (R=-0.50; p < 0.005). In the second turn no significant differences were found in the relation between the variables, while for the final action of the throw a certain negative correlation among the variables existed (-0.39; p < 0.05). Finally, no relation was found between the angular displacement of the hammer and the change in velocity in the double support phase.